Addressing climate change impacts on food supply chain operations: An integrated framework for sustainable optimization - Mirhosseini, Shawn (Journal of Supply Chain Management Science, 2025)
Climate change exerts significant and multifaceted impacts on food supply chains, disrupting operations from production to consumption. This study investigates how climate-related vulnerabilities such as extreme weather events and climatic variability affect the efficiency, cost structure, and overall resilience of food supply chains, with a particular emphasis on disruptions that pose risks to the stability of food supply under uncertain climate conditions. These dimensions remain insufficiently explored in the current literature. To address this gap, a novel multi-objective optimization model is developed, incorporating Climate Vulnerability Indices (CVI) into the strategic planning of food supply chain networks. The model is formulated and solved using GAMS with the CPLEX solver, drawing on parameters derived from prior research in sustainable supply chain management. Results illustrate that integrating the CVI into supply chain decision-making enhances the model's ability to account for climate-related risks, enabling more informed trade-offs among economic, environmental, and social objectives. Moreover, through its adaptive structure, the model promotes the long-term sustainability of food supply chains and supports continuity under climate-induced operational challenges. This study offers an innovative, resilience-focused modeling framework that supports sustainable and adaptive supply chain configurations. The findings underscore the critical need for climate-aware optimization approaches to enhance the resilience and sustainability of food systems amid escalating climate risks.